Implementasi Peran Public Relation Dalam Membangun Reputasi PT Cakrawala Dinamika Energi - Erfina Erfina; Sapta Sari; Vethy Octaviani (Universitas Dehasen Bengkulu, 2023)
This study aims to determine the implementation of the role of public relations in building the reputation of PT Cakrawala Dinamika Energi. This study uses the role theory of public relations (Cutlip 2002: 46) which consists of four roles, namely: communication technician, expert presciber, communication facilitator, and problem solving facilitator and the type of research used is qualitative research. The results of the study show that there are four public relations roles that support the implementation of the public relations role in building the reputation of PT Cakrawala Dinamika Energi, namely the first role of public relations as a communications technician is to build good communication between the public, internal, external and company partners, this is important to prevent adverse impact on the company's reputation in the event of a problem. Second, the role of public relations as an expert presiber is to liaise with a structured public relations department to communicate with the public if there are problems. Third, the role of public relations as a communication facilitator is as an intermediary who maintains a two-way flow of communication between the company and its public, including internal and external. And Fourth, problem solving facilitators in public relations must understand company policies, products, and procedures. The right communication strategy is needed so that the problem has a solution without hurting anyone's feelings.